2016
DOI: 10.1186/s12941-016-0136-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics of carbapenem-resistant Enterobacteriaceae in a tertiary-level reference hospital in Turkey

Abstract: BackgroundEnterobacteriaceae are among the most common pathogens that are responsible for serious community-acquired, hospital-acquired, and health-care associated infections. The emergence and spread of carbapenem-resistant Enterobacteriaceae (CRE) have become an increasing concern for healthcare services worldwide. Infections caused by these bacteria have been associated with significant morbidity and mortality and treatment options have been limited. The rapid and accurate detection of carbapenem resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
63
4
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 28 publications
13
63
4
6
Order By: Relevance
“…Other studies have found UTI-causing CRE to be between 1.4-4.2% in the USA, 18 1.2% in Lebanon, 4.05% in Malaysia, <1% in Singapore, 1.2% in Taiwan and 1.17% in Saudi Arabia. 19 The present study showed that 2.4% of 4861 urine specimens and 10.7% of 1082 Gram-negative isolates were CR-GNB, comparable with other countries. Among them, 22 (0.45%) were CP-GNB, or 19% among CR-GNB and 2% of all Gram-negative isolates.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other studies have found UTI-causing CRE to be between 1.4-4.2% in the USA, 18 1.2% in Lebanon, 4.05% in Malaysia, <1% in Singapore, 1.2% in Taiwan and 1.17% in Saudi Arabia. 19 The present study showed that 2.4% of 4861 urine specimens and 10.7% of 1082 Gram-negative isolates were CR-GNB, comparable with other countries. Among them, 22 (0.45%) were CP-GNB, or 19% among CR-GNB and 2% of all Gram-negative isolates.…”
Section: Discussionsupporting
confidence: 83%
“…NDM‐1‐producing Enterobacteriaceae might carry other mechanisms for antibiotic resistance with various β‐lactamases and other types of carbapenemases resistant to other antimicrobials . We found that 18 strains with bla NDM‐1 were susceptible to MINO, TMP/SMX and TGC than P. aeruginosa strains with bla IMP‐7 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Carbapenemaseproducing Enterobacteriaceae (CPE) are capable of hydrolysing Carbapenems and all other β-lactam antibiotics [5][6][7]. Although plasmid-mediated resistance is not the only mechanism of resistance among CRE, it is the most epidemiologically important due to the high efficiency at which Enterobacteriaceae exchange plasmids among each other [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms for Carbapenem resistance in Enterobacteriaceae include hyper-production of extended spectrum beta-lactamases (ESBLs), class c-β-lactamases (AmpC), mutations in porins and alterations or up-regulation of efflux pumps [6]. The most common Carbapenemases worldwide include the metallo-β-lactamases New Delhi-metallo-β-lactamase (NDM), Imipinemase β-lactamases (IMP), Verona integron encoded metallo-β-lactamase (VIM), Guiana extended spectrum β-lactamases (GES), and Oxacillinase β-lactamase (OXA-48 types) [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%